A multilateral network perspective on inward FDI - Jha, Soni; Awate, Snehal; Mudambi, Ram (Journal of International Business Studies, 2024)
Foreign direct investment (FDI) remains a preferred mode for multinational enterprises to access international markets, resources, and technology. However, there are vigorous debates in the academic literature about the magnitude of inward FDI spillovers and their effect on the economic growth of host countries. In this paper, we argue that these empirical inconsistencies arise from the narrow “home-host” bilateral context in which inward FDI spillovers are analyzed. Further, we show that the inconsistencies can be resolved by adopting a broader, multilateral network perspective to estimate the effects of inward FDI. This perspective allows us to account for the differences in inward FDI spillovers from different investing countries and aggregate these to assess the overall impact of inward FDI. We use quantitative network-centric analysis to model the multilateral connectivity amongst nations engendered by inward FDI. Specifically, we use a panel data set of over 200 host countries spanning two decades to demonstrate that (a) the diversity of inward FDI measured by the number of investing countries and (b) the quality of inward FDI measured by the structural position of investing countries in the global inward FDI network is correlated with higher economic growth of host countries.